2022
DOI: 10.3390/toxins14110743
|View full text |Cite
|
Sign up to set email alerts
|

Does Deoxynivalenol Affect Amoxicillin and Doxycycline Absorption in the Gastrointestinal Tract? Ex Vivo Study on Swine Jejunum Mucosa Explants

Abstract: The presence of deoxynivalenol (DON) in feed may increase intestinal barrier permeability. Disturbance of the intestinal barrier integrity may affect the absorption of antibiotics used in animals. Since the bioavailability of orally administered antibiotics significantly affects their efficacy and safety, it was decided to evaluate how DON influences the absorption of the most commonly used antibiotics in pigs, i.e., amoxicillin (AMX) and doxycycline (DOX). The studies were conducted using jejunal explants fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…As stated in the research objective, this study was conducted to determine if low ZEN doses naturally occurring in feeds could produce similar effects, and the present results suggest that it is possible. This conclusion is also consistent with the results of previous studies conducted as part of the same research project [ 2 , 19 , 29 , 31 , 32 , 33 , 34 , 35 , 36 , 52 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As stated in the research objective, this study was conducted to determine if low ZEN doses naturally occurring in feeds could produce similar effects, and the present results suggest that it is possible. This conclusion is also consistent with the results of previous studies conducted as part of the same research project [ 2 , 19 , 29 , 31 , 32 , 33 , 34 , 35 , 36 , 52 ].…”
Section: Discussionsupporting
confidence: 93%
“…This study confirmed our recent observations that low ZEN doses improve somatic [ 36 ] and reproductive health (our previous mechanistic studies) [ 2 , 19 , 37 ]. On the first day of exposure, ZEN exerted a stimulatory effect on the body, with the exception of the reproductive system [ 18 , 38 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…12 The intestinal epithelium is essential in the formation of a selective barrier between the internal environment and both intraluminal dietary antigens and microbes; increased gut permeability is associated with various inflammatory diseases and disrupted immune homeostasis. 13,14 It has been suggested that DON-induced opening of tight junctions, increases in bacterial translocation, and decreases in mucus production can promote the intestinal epithelial entry of xenobiotics (harmful molecules and pathogenic microorganisms present in food and water) and have additional consequences on systemic immunity and nutritional metabolism. [15][16][17] Furthermore, DON significantly reduces the diversity of gut microbiota, thereby altering host immunity.…”
Section: Introductionmentioning
confidence: 99%
“…Acute poisoning and severe mycotoxicosis are less frequently reported. Complex toxicological interactions (additive effects, synergism, potentiation, and antagonism between mycotoxins) and the dose absorbed [ 17 ] undoubtedly affect health and reproductive processes [ 18 ]. Depending on the absorbed dose, the interactions between co-occurring mycotoxins or between mycotoxins and specific tissues in mammals [ 19 , 20 , 21 ] may require further investigation and risk assessments [ 22 ] based on an analysis of the biological activity of individual mycotoxins [ 12 , 16 , 17 ].…”
mentioning
confidence: 99%